Pengaruh Penggunaan Modul Digital Interaktif Untuk Meningkatkan Hasil Belajar Mahasiswa Pada Mata Kuliah Pembelajaran Braille - Lutfi Isni Badiah; Andri Kurniawan (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
The purpose of this study was to describe the effectiveness of using interactive digital module to improve student learning outcomes in braille course during online lecture. This research design is a pre-experimental research design. The type used is one group pretest-posttest. The subjects of this study amounted to 30 students who took braille course at the Special Education Study Program, Universitas PGRI Adi Buana Surabaya, odd semester 2021/2022. Data collection technique is to use test. While the data analysis technique using the Wilcoxon test. Based on the description of the data and the analysis technique carried out, it can be seen that there is an increase in learning outcomes after students use interactive digital module in braille course. This is evidenced by hypothesis testing with Wilcoxon test analysis which shows the value of Sig. (2-tailde) 0.000 < 0.05. This shows that there is an influence in the use of interactive digital modules in improving student learning outcomes in braille course. In addition, students also admitted that they were more motivated and interested in the learning process